Doctoral Theses on Foreign Languages in Andalusia (2010-2021): A Gender Analysis - Hernández García, Valeria; Maz-Machado, Alexander; Rodríguez, María Josefa (Technium Social Sciences Journal, 2022)
The aim of this article is to study the production of doctoral theses on foreign languages, from our point of view as Spanish speakers, conducted in Andalusia from 2010 to 2021 in order to collect the total number of dissertations and the diachronic distribution; to describe the production per universities, authors and directors according to the gender; and to gather the descriptors most used. Results show that, during the period 2010 to 2021, Andalusian public universities recorded 266 dissertations on FL. The annual average is of 22.16 doctoral theses per year. The representation of women in the authorship of dissertations is 175 (65.78 %), as opposed to 91 men (34.22 %). The participation in the direction of such PhD theses is 51.45 % for women and 48.55 % for men. In accordance with the composition of the direction, doctoral theses were supervised in equal percentage by both only women and (41.35 %) and only men (41.35 %). Mixed direction reached 17.29 %. The amount of 117 different descriptors was gathered. The most used keyword is translation and interpreting (22.7 %). In conclusion, a decrease in the doctoral production on FL was found at Andalusian universities as of 2016. The authorship reveals that FL is a feminised field. In addition, it has been confirmed that mixed co-directions are unusual in this area.